Penelitian âpolymer blendâ high styrene rubber dengan karet alam untuk âsponnge middle soleâ - Setyowati, Penny; Nadilah, Sri; Nurwati, Nurwati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The objective of this research was find optimum composision of polymer blend of High Styrene Rubber (HSR) and Natural Rubber (SIR 3L) for preparation sponge middle sole that save the best fisical properties, strong, flexible, light, stable and thermoplastic properties. The formulation of rubber compound has to be researched as much as 3 formalition MS 1, MS IIÂ and MS III with variation of SIR 3L, HSR and HAF black as follows, MS I 70-30-20 phr ; MS II 80-20-30 PHR and MS III 90-10-40 phr . From the fisical test analysis, optimum formulation to be reached at the compound formualtionÂ MS III with result of fisical test as follows : Tensile strength : 0.572 kg/mm2 ; Elongation at break : 204% ; Hardness share A : 55,8 : Density 0,728 gr/cm3 : Tear Resistance : 0,296 kg/mm2 and Compression Set 22,042%.Â Â INTISARI Â Tujuan penelitian ini adalah menentukan komposisi optimum âPolymer blendâ dariÂ âHigh Styrene Rubberâ (HSR) dengan karet alam SIR. 3L untuk pembuatan âspnge middle soleâ yang memberikanÂ sifat-sifat fisika yang baik, kuat, lentur, ringan, stabil dan bersifat termoplastik. Formulasi kompon karet yang telah diteliti sebanyak 3 formulasi dengan variasi jumlah SIR 3l, HSR dan âHAF blackâ sebagai berikut :Â MSI : 70-30-20 PHR : MS II = 80-20-30 phr dan MS III: 90-10-40 phr. Dari analisa uji fisika diperoleh hasil bahwa formulasi optimum dicapai pada MS IIIÂ dengan hasil uji sebagai berikut. Tegangan putus = 0,572 kg/mm2; perpanjangan putus ; 204% ; Kekerasan Share A = 5,8 ; Bobot jenis = 0,728 gr/cm2, Ketahanan Sobek = 0,296 kg/mm dan PampatÂ tetap 22,042%.Â